Building Collaboration through WhatsApp: Effective Communication Practices of Teachers to Parents in Early Childhood Education Institutions - Hasanah, Nor Izatil (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri (UIN) Syekh Wasil Kediri, Indonesia, 2025)
Effective communication between teachers and parents is an important factor in supporting optimal early childhood development. This article describes communication practices on WhatsApp between teachers and parents to support child development and the challenges that arise in the process. The research method is a descriptive qualitative case study. Data were collected through semi-structured interviews with two teachers at the Raudatul Ilmi Kindergarten. The collected data were analysed using condensation techniques, data display, and conclusion drawing/verifications. The results of the study showed that WhatsApp facilitated the exchange of information about children's learning development, the coordination of activities, the documentation of children's activities at school, to disseminate information regarding unexpected occurrences affecting students, parents employ WhatsApp to report their children's absences from school and the building of closer partnerships. However, although WhatsApp makes communication easy, several challenges arise, such as miscommunication and uneven intensity of WhatsApp use among parents.